Control interno en el departamento administrativo y su incidencia en la toma de decisiones de la agrícola bananera Dánica Fruits S.A. del cantón Valencia, provincia de Los Ríos, año 2021. - Chusin Soatunce, Alba Sofia (2021)
This work is carried out in the canton of Valencia, with the objective of making an evaluation of internal control and proposing a manual of functions and procedures in the administrative department. For this, an applied research was used, of a documentary and field bibliographic type, with which the search for information was carried out for the elaboration of the theoretical framework and data collection necessary to fulfill the objective of this research, the application of the techniques such as the interview and the survey, instruments such as the questionnaire. It can be said that the company at a professional level is on the right track, with a view to expanding, but internally there are certain difficulties in what has to do with administrative matters caused by deficient internal control; Among the results of the evaluation, it is obtained that the banana farm does not have an established mission, vision and values, which prevents planning the objectives to be achieved, on the other hand it does not have the organizational structure and manual of functions and procedures; the elaboration and application of the questionnaires are fundamental pieces to protect the resources of the company, giving us as a result a confidence level of 64% qualified as "moderate", while the level of control risk is "low" with 18% and the inherent risk of 36% considered with the same rating level as the control risk. According to the objectives established in this research, the management indicators were evaluated; efficiency giving us a percentage of 33, 33% which represents how the lack of a manual affects agriculture; According to the calculation made, the administrative staff complies with the activities in 62.50% and efficiency with 20.83%, so we can determine that the banana farm has a low level of efficiency, for these reasons corrections must be made necessary and provide solutions to each of the findings in terms of internal control, knowing that with this you have the opportunity to obtain a more stable, efficient and effective company focusing on safeguarding company resources. A structural organization chart and a manual of functions and procedures for the administrative department were also established, which are of great help to the company because they facilitate us to delimit the functions of each person, through the segregation of functions.